Study on fatigue damage laws and life prediction of CRTS-II ballastless track slab. (1st February 2022) - Yang, Yang; Zhang, Guanjun; Wu, Gang; Cao, Dafu
Highlights: Investigate the fatigue performance of CRTS-II ballastless track slab. The fatigue damage laws and fatigue life of CRTS-II ballastless track slab is significantly affected by fatigue load level. Mechanical behavior of CRTS-II ballastless track slab specimen S-RC1 is observed by FEA models. Proposed fitted formula could predict the fatigue life of the slabs under both constant amplitude fatigue load and variable amplitude load. Abstract: To analyze the fatigue damage laws and fatigue life prediction, six full-size CRTS-II ballastless track slabs were tested under fatigue cyclic loading conditions. The main parameter considered was the fatigue load level that ranged from 0.5 to 0.675 P u (the ultimate static capacity). The results indicate the following: (1) the slab under the load level of 0.5 P u showed a slight reduction in capacity and deflection after 3, 000, 000 cycles, and its residual strength was only reduced by 3%. (2) the fatigue limit of the slab cannot exceed 0.6 P u (survived 2, 000, 000 cycles), because the stiffness and the residual deflection of the slab increased significantly at the increased the load level. (3) Based on the Palmgren-Miner cumulative damage criterion and the test results, the fitted formulas obtained from experimental results can predict the fatigue life of the slabs under both constant amplitude fatigue load and variable amplitude load.